A word derived from a verb and used as an adjective is called a ______, as seen in the following example:
Gnarled and twisted, the old oak seemed like it would last forever.
modifier
adverb
participle

A word derived from a verb and used as an adjective is called a participle, as seen in the following example: Gnarled and twisted, the old oak seemed like it would last forever.

s

Question

Asked 10/4/2012 10:41:29 AM

Updated 12/10/2018 2:04:21 PM

1 Answer/Comment

Edited by Masamune [12/10/2018 2:03:50 PM]

Rating

3

A word derived from a verb and used as an adjective is called a **participle**, as seen in the following example: Gnarled and twisted, the old oak seemed like it would last forever.

Added 12/10/2018 2:04:21 PM

This answer has been confirmed as correct and helpful.

A word derived from a verb and used as an adjective is called a ______, as seen in the following example:
Gnarled and twisted, the old oak seemed like it would last forever.

Question

Updated 1/19/2014 1:47:46 PM

1 Answer/Comment

A word derived from a verb and used as an adjective is called a PARTICIPLE, as seen in the following example: Gnarled and twisted, the old oak seemed like it would last forever.

Added 1/19/2014 1:47:46 PM

This answer has been confirmed as correct and helpful.

A word derived from a verb and used as an adjective is called a what as seen in the following example:
Gnarled and twisted, the old oak seemed like it would last forever.

Question

Updated 1/19/2016 6:00:19 PM

1 Answer/Comment

A word derived from a verb and used as an adjective is called a Participle, as seen in the following example: Gnarled and twisted, the old oak seemed like it would last forever.

Added 1/19/2016 6:00:19 PM

This answer has been confirmed as correct and helpful.

Confirmed by Janet17 [1/19/2016 6:08:40 PM]

-5x + x + 9 = -4x + 12 **Weegy:** The answer is x=-6,2. [ x^(2)-12=-4x
Since -4x contains the variable to solve for, move it to the left-hand side of the equation by adding 4x to both sides.
x^(2)-12+4x=0
Reorder the polynomial x^(2)-12+4x alphabetically from left to right, starting with the highest order term.
x^(2)+4x-12=0
In this problem 6*-2=-12 and 6-2=4, so insert 6 as the right hand term of one factor and -2 as the right-hand term of the other factor.
(x+6)(x-2)=0
Set each of the factors of the left-hand side of the equation equal to 0.
x+6=0_x-2=0
Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.
x=-6_x-2=0
Set each of the factors of the left-hand side of the equation equal to 0.
x=-6_x-2=0
Since -2 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 2 to both sides.
x=-6_x=2
The complete solution is the set of the individual solutions.
x=-6,2 ] (More)

Question

Updated 6/7/2014 2:18:52 PM

2 Answers/Comments

-5x + x + 9 = -4x + 12;

-4x + 9 = -4x + 12;

-4x + 4x = 12 - 9;

0 = 3

For equation -5x + x + 9 = -4x + 12, there is no solution that exists.

-4x + 9 = -4x + 12;

-4x + 4x = 12 - 9;

0 = 3

For equation -5x + x + 9 = -4x + 12, there is no solution that exists.

Added 6/7/2014 2:18:44 PM

This answer has been confirmed as correct and helpful.

31,997,640

questions answered

There are no comments.